Promoting the learning of Hijaiyah letters for a child with Down syndrome using plasticine media - Abdul Azis; Yayan Nurbayan; Maskanatul Fiqiyah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2024)
The difficulties in reading the Qurâ€™an experienced by children with special needs did not receive adequate attention. There is a gap in the ability to read the Qurâ€™an between children with special needs and normal children. This research aims to describe the use of plasticine media to support the learning of Hijaiyah letters for a down syndrome child. This research used a descriptive qualitative method. The data were collected through observation and interview. The data analysis included three stages, namely data reduction, data presentation, and conclusions. The results show that learning Hijaiyah letters using plasticine has a significant impact on a child with down syndrome. The three-dimensional letters formed using plasticine media are more recognizable to a child with down syndrome. Before using plasticine, the child could not recognize and pronounce the Hijaiyah letters independently. However, he could recognize and pronounce the Hijaiyah letters independently without assistance after using plasticine. The child's understanding of the Hijaiyah letters also improves. He can differentiate one letter from another, such as noticing the number of dots in the letters Ba, Ta, and á¹ a. Using plasticine media in the learning process can increase the childâ€™s enthusiasm for learning, develop his imagination, and support his memory.Keywords: Hijaiyah letters, media plasticine, down syndrome